Border carbon adjustments: rationale, design and impact. (19th October 2022) - Keen, Michael; Parry, Ian; Roaf, James
Abstract: This paper assesses the rationale, design and impact of border carbon adjustments (BCAs). Large disparities in carbon pricing between countries raise concerns about competitiveness and emissions leakage. BCAs are potentially the most effective domestic instrument for addressing these challenges – but design details are critical. For example, limiting coverage of the BCA to energy‐intensive, trade‐exposed industries facilitates administration, and initially benchmarking BCAs on domestic emissions intensities would ease the transition for trading partners with emission‐intensive production. It is also important to consider how to apply BCAs across countries with different approaches to the mitigation of emissions, and the treatment of exports. BCAs alone do not solve the free‐rider problem in carbon pricing, but might ease it, and be a step towards an effective international carbon price floor.